Strategic use of environmental information - Geir B. Asheim (University of Oslo, Department of Economics, 2009)
Strategic use of environmental information may have as consequence that a benevolent environmental agency will choose not to disclose information leading to reduced moral motivation. Thus, decision makers will not have access to such information, implying that they will not be able to adjust their decisions to available information on the state of the environment. In contrast, if the benevolent environmental agency instead bases its regulation on standard economic instruments, these instruments will incorporate all available information.
Keywords: D11; H41; 330; Environmental regulation; voluntary contributions; moral motivation; hard information; Umweltauflage; Informationsmanagement; Ethik; Motivation; Wohlfahrtseffekt; Theorie